177k views
0 votes
Solve 6x^2 +5x - 4 = 0 by factoring. Enter each step. please help me.

User Chani
by
4.4k points

2 Answers

3 votes

Answer:


(1)/(2) and
-(4)/(3)

Explanation:

We can solve this equation using the quadratic formula, which is


\frac{{ - b \pm \sqrt {b^2 - 4ac} }}{{2a}}}

Assuming that with your equation, 6x² + 5x - 4 = 0, a is 6, b is 5, and c is -4.

We can substitute inside the equation.


\frac{{ - 5 \pm \sqrt {5^2 - 4 \cdot 6\cdot\-4} }}{{2 \cdot6}}}


\frac{{ - 5 \pm \sqrt {25 + 96} }}{{12}}}


\frac{{ - 5 \pm \sqrt {121} }}{{12}}}


\frac{{ - 5 \pm 11 }}{{12}}}

Now, we can find our two values by using subtraction/addition and division.


-5 + 11 = 6\\-5 - 11 = -16


(6)/(12) =(1)/(2) \\-(6)/(12) =-(4)/(3)

I hope this helped!

User Akbarali
by
4.7k points
5 votes

Answer:

x = -4/3 x =1/2

Explanation:

6x^2 +5x - 4 = 0

6 has factors of 3 and 2 and 6 and 1

4 has factors of -4 and 1 and -2 and 2, and -1 and 4

We want +5 in the middle

3* -1 + 4*2 = 5

( 3x+4) ( 2x -1) =0

Using the zero product property

3x+4 =0 2x-1 =0

3x = -4 2x =1

x = -4/3 x =1/2

User Chethan
by
4.8k points